Effect of recorded maternal voice on procedure pain - a double blinded randomized controlled trial - Deeksha Patel; Cecilia M.S; Aditi Prashant Sinha; Sameer Bakhshi (lppm Universitas Muhammadiyah Semarang, 2024)
This double-blinded randomized controlled trial included 46 children between 4 to 12 years of age with haematological malignancy, scheduled for bone marrow examination at tertiary care hospital of India. Subjects were enrolled into two groups (23 each) by stratified random sampling based on the type of procedure scheduled to them. The maternal voice was recorded for 3 minutes before the procedure and headphones was placed during the procedure, for all children but maternal voice was played only to intervention group by another person to blind the researcher. Child's cooperation for the entire procedure was recorded as video by researcher and later video was rated using FLACC behavioural scale. Pain perception was rated by children using Wong-Baker faces pain rating scale. The results showed a significant difference in the level of child's cooperation with mean (SD) distress score of 7(2) in control group and 4.52(2.15) in the intervention group (p=0.0002). There was no significant difference in pain perception of control and intervention groups. Significant moderate positive correlation (0.31) was found in the child's distress and pain perception levels (p=0.03). There was significant negative association of age was found with the child's distress (-0.30) and pain perception level (-0.33) at (p=0.04, 0.02) respectively. In cconclusion, recorded maternal voice can significantly decrease the child's distress level thus improve the child's cooperation during bone marrow examination along with local anaesthesia.  As the child's cooperation increased, the child perceived less pain during the procedure. Older children were more cooperative and perceived less pain as compared to younger ones. Nurses are at an ideal position to implement this cost-effective, non-pharmacological intervention for children undergoing bone marrow examination.